Sentimental direction in promiscuity poetry at the first Abbassi age - حيدر, محسن; حكمت عيسى; طلال حسن (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The sentimental trend in the general sense represents the attitude of poets - artistic - to life, nature and society, and what distinguishes sentimental poetry from other poetry trends is the emergence of the poet's self and emotions, his emotions, the manifestation of the ripples of this self, and the special attitudes of life, nature, religion society, universe and poetry He came up with a distinctive poetry template, and with influential art. The poetry promiscuity of the first Abbasy age are the poetry of envelope, obscene and rebellion in which he seeks and through which to prove himself and expressing his feelings, tendencies, wishes, thoughts, attitudes to life, society, religion and the universe intellectual, religious, social and artistic rebellion, bearing the dimensions of civilization, culture and history of that time. The phenomenon of promiscuity is a problematic issue for researchers and scholars of Arab literature because it carries with it revolution, rebellion, rejection, disregard, extremism and self-proof, Departing from the Decade of Religion, Power and Society, but it has rich and serious beverages that distinguish it from most of the poetry of that age that glorified the group/tribe, He is sacred to his feet and lives in an ambience between their times and its attributes, as evidenced by the appearance of the poet's personality through his artistic expression of his emotions, emotions and pursuit of autonomy.